Development of Irrigated Agriculture in the Rural Areas of the Southern Suburbs of Meknes between the Requirements of Sustainable Rural Development and the Challenges of Water Stress (Journal of Libya for geographical studies, 2026)
A set of natural and historical factors has interacted to shape the agricultural landscape in the rural areas south of the city of Meknes. The irregularity of rainfall and the lack of a permanent surface water network have played a prominent role in directing agricultural practices toward irrigation as a strategic option to achieve agricultural intensification, particularly given that the region lies within the Saïss Plateau, which is rich in groundwater resources. In their search for alternative water sources, farmers have increasingly relied on the unconfined aquifer through the drilling of irrigation-equipped wells, with depths ranging from about 50 m in the northern part of the southern suburbs to approximately 80 m in the far south. It is well established that the rapid increase in the number of wells has had negative impacts on groundwater resources, which have been experiencing a continuous decline in water reserves at an average rate of about 40 cm per year. This has been accompanied by a drop in the groundwater table, with an estimated annual average decline of around 4 m. In addition, surface water inputs have decreased, as groundwater recharge amounts to approximately 240 million m³, while withdrawals reach about 340 million m³, resulting in an annual deficit of nearly 100 million m³. In response to these transformations, the irrigated agricultural area in the region has expanded significantly over the past two decades by approximately 4,300 ha, with an uneven spatial distribution. The largest expansion occurred in the municipality of Majjat (1,670 ha), followed by Sidi Slimane Moul Al-Kifane (1,430 ha) and Ait Yaazem (1,200 ha.( At the same time, the area of land suitable for agriculture has declined. Despite this dynamic expansion, rainfed subsistence agriculture remains important, which signals a likely further shift toward irrigation and increased pressure on the underlying groundwater aquifer. This trend poses a serious threat to regional water security and is associated with a range of environmental problems. The study highlights the urgent need to reconcile irrigated agricultural development with the principles of sustainable rural development and integrated water resource management.
Keywords: Rural areas south of Meknes; water resources; irrigated agriculture; agricultural land use; sustainable development